Health worker experience of heat-related discomfort, service delivery, and related coping and adaptation in Ghana - Delali Benjamin K. Dovie; Lois Antwi-Boadi; Abena Fosuaa Ofosu Koranteng; Wilhemina Quaye; Margaret Appiah (Discover Public Health, 2026)
Abstract Introduction Mean daily temperatures are rising and may affect health system functioning, yet evidence remains limited on how health workers experience and respond to heat-related discomfort across interconnected health system domains. This study explored health workers’ experiences of how heat-related discomfort influences workforce functioning, service delivery, and health infrastructure, and related governance and adaptation within Ghana’s health system. Methods Eighteen focus group discussions and fifty-six key informant interviews were conducted with health directors, facility managers, nurses, and public health officers across six regional clusters. The WHO Health System Building Blocks framework guided the thematic data analysis using MAXQDA, with inductive coding to identify emerging patterns. Results Heat-related discomfort was associated with fatigue, dehydration, reduced concentration, and challenges in maintaining regular work attendance and routines. Poor ventilation and unreliable power supply were perceived to intensify indoor heat, constrain usable workspace, and create challenges for medicine and vaccine storage. Effects of heat on service delivery included congestion, staff absenteeism, shortened consultations, and irregular patient attendance. Although formal governance and financing mechanisms for heat preparedness were perceived as limited, health workers described a range of behavioural, operational, and facility-level responses, including adjusting work schedules, triaging patients, reorganising workspaces, and planting shade trees. Conclusion Participants’ experiences of strengthening heat preparedness may benefit from integrating heat management into occupational health regulations, improving facility design and ventilation, and providing resources for climate-related adaptation. Such measures could help support the continuity and resilience of health service delivery under rising temperatures.